Development of Elementary School Islamic Religious Education Textbooks Class IV Comic Based - Agus Santri; Ali Imran Sinaga; Salim Salim (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2020)
This study aims to develop a grade IV comic-based Islamic Religious Education textbook as well as to determine the level of eligibility and effectiveness of its use. Initial product development is carried out through preliminary studies in the form of needs analysis and curriculum analysis. The feasibility test was carried out by a questionnaire assessment by three experts, namely material experts, media experts, and comic experts. The effectiveness level of the product can be known through individual, group trials and field trials. The research method used is the R and D or research and development method, with six steps of development, starting from the initial study, initial product, expert validation, individual and group testing, and field testing to the final product. The result is a product in the form of a comic-based grade IV Islamic Religious Education elementary school textbook that is very feasible and effective. The average score for the feasibility test was 90.05% in the Very Eligible category, while the average score for the effectiveness test was 88.67% with the Effective category.